Distinct negative regulation of the human embryonic globin genes zeta and epsilon. - Watt, P; Lamb, P; Proudfoot, N (1993)
The human embryonic globin genes zeta and epsilon are expressed when erythropoiesis is initiated at about the third week of development but are subsequently repressed as expression of the fetal globins, alpha and gamma, begins. We have examined the promoter region of the human zeta-globin and epsilon-globin genes in order to identify regulatory sequences that may be involved in this process. Stable transfection of the human erythroid cell line K562 with either a truncated form of the zeta-globin gene, containing 112 base pairs (bp) of 5'-flanking sequences, or a larger zeta-globin construct, containing several hundred bp of 5'-flanking sequence, revealed that the zeta-globin gene is subject to negative regulation by its 5'-flanking region. We have defined the sequences responsible for this negative regulation to a 22 bp region immediately upstream of the proximal promoter sequence of the zeta-globin gene. A 22 bp oligonucleotide including this negative element was found to inhibit both the zeta-globin and HSV TK promoters. We have also analyzed the promoter of the human epsilon-globin gene, since it is coordinately expressed with zeta-globin. We show that it is likewise subject to negative regulation, though in this case from a distal silencer element. Gel retardation and methylation interference assays have provided evidence of a factor which binds specifically to the epsilon-globin silencer. However, no obvious sequence homology exists between the zeta and epsilon negative elements, and at least some of the factors that recognize these elements are distinct. We postulate that the negative transcriptional control elements in the human embryonic globin gene promoters contribute to the observed reduction in zeta- and epsilon-globin gene expression that occurs during development.